BIOGRAPHICAL APPROACH TO HUMAN RESOURCE MANAGEMENT - Ratković Njegovan, Biljana (International Journal of Economic Practice and Policy, 2015)
The paper discusses the importance of biographical approach to managing human resources, which is especially important in the first, anticipatory stage of organizational socialization, in which interview for the job is performed. Biographical principle is based on a broader and more complex approach to the candidate, which enables him to present his working career, personal qualities, professional knowledge and skills, social skills, interests and aspirations. Biographical approach allows an individual who has applied for a certain job to reflect, identify and present their work and life path in their own way.. The organization, in turn, through the biographical method receives valid information to predict the future behavior of candidates and their performance.
Keywords: biographical method; human resources management; selection; anticipatory phase of organizational socialization; self-identification